PEMBINAAN KELUARGA DALAM PERSPEKTIF JAMAAH TABLIGH - Kamalludin, Kamalludin (JURNAL ILMU SYARIAH, 2014)
Coaching Family In Tablighi Jamaat. Khuruj in Tablighi Jamaat are madrassas preaching trip to establish the nature of the self graduallyimaniyyah culprit. Expected to experience this propaganda effort, the help of God will always be there at any time and the cause of God's guidance for the universe will end up with Khusnul Khatimah. But in practice it takes a balance between preaching and family coaching. Because Khuruj requires one to come out leaving his family in a certain time frame. So then it takes a balance between preaching and coaching families, in addition to the support of his wife and children to overcome various problems at the time the head of the household was Khuruj Fi Sabilillah.